The long-term economics of climate change beyond a doubling of greenhouse gas concentrations - Hall, Darwin C.; Howarth, Richard B. (Emerald, 2001)
This volume will include scenarios of geophysical and economic impacts from global warming beyond a doubling of greenhouse gases. Analyses will examine geophysical, ecological, and economic impacts, physical and institutional lags, alternative scenarios with and without policy intervention, institutional change, political-economic barriers to effective policy, and prescriptions for change. Perspectives will include those from physical and biological sciences, as well as economics.
Keywords: Environmental economics.; Natural resources.; elektronické knihy; electronic books